Pengaruh Gaya Kepemimpinan dan Motivasi Terhadap Produktivitas Kerja Karyawan Departemen Produksi PT. Intikemas Putra Makmur di Jatiuwung - Deni Rahmadinata; Bambang Libriantono (Komunitas Dosen Indonesia, 2021)
Leadership style and work motivation are very closely related to employee work productivity, which means that good work productivity is achieved in a company because of the efforts made by a leader and the existence of work motivation in employees. In a company, the problem of work productivity is something that is very important and must be considered by looking at several supporting factors that are considered influential, including leadership style factors and work motivation factors. This study aims to determine whether there is an influence of leadership style and motivation on work productivity of production department employees of PT. Intikemas Putra Makmur. The method used in this study is a quantitative method, with data collection techniques using questionnaires, interviews, observation and literature study. in collecting data. The number of samples in this study were 72 respondents. Then the test tool used is SPSS software. The research results obtained in this study indicate that Leadership Style has a moderate and significant relationship to Employee Productivity with a correlation coefficient of 0.568. Work Motivation has a weak and insignificant relationship to Employee Productivity with a correlation coefficient of -0.142. This shows that Leadership Style plays an important role in increasing employee productivity. In addition, work motivation also has an influence on work productivity, although not as strong as leadership style. So it can be concluded that leadership style has a strong and significant relationship to employee work productivity, while work motivation has a weak and insignificant relationship